1993
DOI: 10.1016/s0002-9610(05)80519-7
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic insulinomas

Abstract: We report a series of 30 patients with pancreatic insulinoma treated from 1967 to 1990. Twenty-nine patients underwent surgery. In 24 patients, the lesion was a benign adenoma. The pancreatic lesion was localized preoperatively in 59% of cases (94% since 1980), and all lesions that were identifiable histologically were palpable intraoperatively. Endoscopic pancreatic ultrasonography, performed twice, appeared to be a very promising method of investigation. In the 24 patients with adenoma, 14 enucleations and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
14

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 18 publications
2
15
0
14
Order By: Relevance
“…Nonetheless, pancreatic fistulas were detected in 5 of 21 (24%) patients after enucleation, 4 of which had minimal clinical impact (Grade A). This compares favorably to other series that report pancreatic fistula rates as high as 57% after enucleation 3,32 Of note, 7 of 21 (33%) patients treated by enucleation had positive margins on histology. None had recurrence at the site of enucleation on long-term follow-up.…”
Section: Discussionsupporting
confidence: 77%
“…Nonetheless, pancreatic fistulas were detected in 5 of 21 (24%) patients after enucleation, 4 of which had minimal clinical impact (Grade A). This compares favorably to other series that report pancreatic fistula rates as high as 57% after enucleation 3,32 Of note, 7 of 21 (33%) patients treated by enucleation had positive margins on histology. None had recurrence at the site of enucleation on long-term follow-up.…”
Section: Discussionsupporting
confidence: 77%
“…Doherty et al (27) have identified 64% of insulinomas by means of palpation. Machado et al (16) have reported the detection of 98.2% of cases by means of inspection/palpation, a result similar to those of other authors (35)(36)(37) . The literature review demonstrates that smaller the lesions to be evaluated, the greater will be the limitations of preoperative examinations.…”
Section: Introductionsupporting
confidence: 81%
“…1 Other localization studies have been used, including preoperative ultrasonography, transgastric endoscopy, computed tomography (CT), magnetic resonance (MR) imaging, radionuclide scanning, transhepatic venous catheterization, and calciumstimulated angiography with catheterization of hepatic veins. [2][3][4][5] Despite the many attempts aimed at localizing insulinomas, the tumors remain undetected in about 40% of patients. 6 The purpose of this study was to review the results of the localization techniques in 66 consecutive patients who were surgically treated for insulinomas at University of California, San Francisco, from 1975 to 1998.…”
mentioning
confidence: 99%